Research progress in integrated thermal management of electric vehicles - Meng-liang YAO; Yun-hua GAN; Jia-lin LIANG; Yong LI (工程科学学报, 2020)
Severe energy crisis and environmental pollution are the foremost problems in the world today. Electric vehicles have several advantages over traditional internal combustion engine-based vehicles, such as high energy efficiency and low emissions, which are effective in alleviating the energy crisis and environmental problems. However, the electric vehicles’ performance is greatly affected by temperature. An excessively high temperature during the charging and discharging process may accelerate the degradation rate of a battery cell and shorten its lifespan. In contrast, an excessively low temperature may reduce the battery’s efficiency and affect its discharge capacity. Air-conditioning systems in electric vehicles consume electricity to create a comfortable environment in the passenger compartment. However, excessive temperature of the motor drive will decrease its efficiency. Therefore, the battery, passenger compartment and motor drive system must be maintained at adequate temperatures to ensure the safety, comfort, and economy of the electric vehicles. Previous studies usually focused on a single thermal management system at a time, such as a battery thermal management system, air-conditioning systems in electric vehicles, and motor thermal management system. This means that the coupling relationships between the above-mentioned thermal management systems and the performance analysis of the integrated thermal management system at the vehicle level were not properly investigated. This study focused on the key issues in the construction of an integrated thermal management system for electric vehicles. Firstly, the heat generation models of the battery, passenger compartment, and motor drive system were summarized. Secondly, the existing thermal management methods for these three systems were systematically reviewed. Especially, the research status, operation control, and performance evaluation of the integrated thermal management system were especially analyzed. Finally, the deficiencies of the previous studies were summarized and the research prospects were proposed. It is pointed out that it is necessary to study the accurate heat generation models, develop the compact and efficient integrated thermal management system, and optimize the operation control of the integrated thermal management system under a comprehensive performance evaluation system in the near future.